Onomástica genérica roncalesa ligada a casas y edificios - Lopez-Mugartza Iriarte, Juan Karlos (Huarte de San Juan. Filología y Didáctica de la Lengua, 2017)
The objective of this article is to show the generic lexicon of the Valley of Roncal in Navarre linked to the oiconimy, science that studies the names of the houses. It means that the proper names of the houses are not mentioned, nor of the constructions of the valley, but the generic names of those houses and those buildings are studied according to the use that is given to them (place of human habitation, resting place for livestock, etc.), the elements that compose it (drains, roofs, chimneys, etc.) and the elements that surround it (orchards, spaces between houses, roads, streets, neighborhoods, etc.). The present work is based on the study of the documentation collected in the Roncal archives and in its comparison with the live speech that has been collected through an oral survey. The lexicon linked to the house and rural buildings is being lost. Some words collected in the documentation or are no longer used, or are not remembered, or are only present in the vocabulary of older people. This article aims to recover these voices from oblivion.
Keywords: Onomastics; oiconimy; toponimy names; Navarre; Roncal; lexicon